Comparison of the Effects of Teaching Games for Understanding (TGFU), Sport Education (SE), and Combined Approaches on Skill Performance in Football among 10 to 12-Year-Old Students - Naeimifar, Raziyeh; Balali, Marziyeh; Parvinpour, Shahab (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The focus on introducing new teaching methods that are both highly effective and enjoyable for children has attracted the attention of many researchers. This study aimed to examine the impact of the Teaching Games for Understanding (TGfU) approach, Sport Education (SE), and Combined Approach on skill performance in children's football. Methodology: The statistical population included all 10 to 12-year-old boys attending schools in Tehran. From this population, 60 students were purposefully selected from a non-profit school and randomly assigned to three groups: TGfU, SE, and Combined Approach (each consisting of 20 students). All participants completed a pre-test, which involved a 4v4 football game on a small pitch measuring 25x35 meters, recorded by a camera. Each group then received their respective training for 5 weeks, with 3 sessions per week (totaling 15 sessions). After the interventions, a post-test, identical to the pre-test, was conducted. Performance was evaluated using the G-PET tool and relevant forms, with recorded videos reviewed by an experienced coach to score performance, including the frequency of sporting behaviors. Findings: The results indicated that all three approaches—TGfU, SE, and the Combined Approach—significantly improved football performance in both correct and incorrect situations (P ≤ 0.05). Furthermore, comparisons among the three groups revealed that the TGfU group performed the best, followed by the Combined Approach group, and then the SE group. Conclusion: The findings suggest that the TGfU and Combined Approach are more effective than traditional Sport Education. Therefore, it is recommended that these methods be utilized in teaching football to children.